USE OF GENERALIZED INDICATORS OF ELECTRICITY CONSUMPTION IN THE ENERGY MANAGEMENT SERVICE OF THE ENTERPRISE (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
In the energy management service of an enterprise, the use of generalized indicators of electricity consumption can be beneficial. These indicators provide a standardized measure of energy usage and can help identify trends, compare performance across different time periods or facilities, and benchmark against industry standards.